EKSTRAKSI KATEKIN DARI DAUN GAMBIR (Uncaria gambir roxb) DENGAN METODE MASERASI - Desta Donna Putri Damanik, Nurhayati Surbakti, Rosdanelli Hasibuan (Jurnal Teknik Kimia USU, 2014)
Catechins are a major components in the plant gambier. Beside catechins, there are several other components such as acid catechu tannat, quersetin, red catechu, gambier flouresin, fats and waxes. More than 80% of  gambier production in Indonesia comes from the province of West Sumatra and North Sumatra, mainly in Limapuluh and Pakpak Bharat. Extraction of catechins from gambir leaf was performed by means of maceration that is soaking with a solvent polar. Maceration is carried out by temperature variations, 30°C, 40°C, 60°C and 80°C; maceration of time that is 1 hour, 6 hours, 12 hours, and 24 hours; and the type of solvent is aquadest, 96% ethanol, 95% ethyl acetate, and a mixture of 96% ethanol and 95% ethyl acetate (1:1). The results were filtered to obtain the filtrate which is then concentrated by rotary vacuum evaporator to test the levels of catechins, moisture content, and ash content. Based on this research the highest levels of catechins obtained the maceration temperature operating conditions of 60 ° C with a time of 6 hours maceration and used  95 % ethyl acetate as solvents in the amount of 87.14 % to 0.925 % moisture content and ash content of 0.04 % .